STRATEGI RUSIA MELALUI RUSSIA’S NEW ARCTIC STRATEGY (2008-2013) - Syinthia Fawaati; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study analyzes the reason of Russia strategy through “Russia’s New Arctic Strategy”.Russia adopted “The Foundations of the Russian Federation State Policy in the Arctic until2020 and beyond”. Based on this document, Russia implements strategies in all areas thatare specific to the Arctic Ocean. Since the release of the document, the role of Russia in theArctic Ocean has increased. The Timeframe begins in 2008, when the document adopted, andends in 2013. This study uses a qualitative research method that source data are taken frombooks, journals, news papers and valid news. This study uses state level analysis. The authoruses a realist perspective and the theory of Graham T. Allison on Rational ActorModel.Russia shows its role in the Arctic Ocean in several sector, such as natural resourcesstrategy, Northern Sea Route strategy, military strategy and environmental strategy. Theseimplementation of the entire strategies aimto Russia's national interest that include naturalresources, Northern Sea Route,territorial security and the environmental security.Key Word: Arctic Ocean, Foreign Policy, National Interest, Russia’s New ArcticStrategy.